Ontology Of Pengembangan Masyarakat Islam (PMI) Da'wah Science In The Community Development Approach - Ahmad Husna; Rini Setiawati; Abdul Syukur (EDUCATIO: Journal of Education)
This research aims to understand the potential and impact of integrating the science of Islamic propagation (Ilmu Dakwah) within the context of Islamic Community Development (Pengembangan Masyarakat Islam - PMI) in a Community Development approach. It explores the fundamental concepts of Ilmu Dakwah PMI and Community Development and investigates how their integration can bring about positive change within Muslim communities. The study identifies several benefits, including increased community participation, sustainable development, and enhanced religious understanding, but also highlights challenges such as resistance to change, conflicting interpretations of religion, and logistical aspects in implementation. Additionally, it underscores the significance of a deep understanding of social and cultural contexts, as well as the role of information technology, especially social media, in the success of this integration.  This research demonstrates how the integration of Ilmu Dakwah PMI with Community Development combines Islamic values, propagation methods, and community development principles to enhance the quality of life for Muslim communities. The advantages of this integration include increased community participation, sustainable development, and a better understanding of religion. However, challenges such as resistance to change, conflicting interpretations of religion, and logistical aspects must be addressed. A deep understanding of local culture and the effective use of information technology, particularly social media, also play pivotal roles in the success of this integration.